2015
DOI: 10.1080/10942912.2015.1042111
|View full text |Cite
|
Sign up to set email alerts
|

Texture Quality Analysis of Rainbow Trout Using Hyperspectral Imaging Method

Abstract: In this study a Hyperspectral Imaging System (Short Wave Infrared range from 1000 to 2500 nm) was used to model fish texture by experimental compression test. Partial Least SquareDiscriminate Analysis modeling technique was used for classifying the samples by linking the hyperspectral information and their measured texture. The R 2 of cross validation and prediction were 0.97 and 0.96, respectively. The Root Mean Squared Errors for cross validation and prediction were 0.07 and 0.09, respectively. Sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The regression model of drying rate has a coefficient of determination ( R 2 ) of 0.9876, adjusted R 2 of 0.9717 and RMSE of 0.0775. The good statistical indexes ( R 2 and RMSE ) suggests the experimental data conform to the model (Abasi, Minaei, & Khoshtaghaza, ; Khoshtaghaza, Khojastehnazhand, Mojaradi, Goodarzi, & Saeys, ). Drying rate is influenced by the cold plasma pretreatment time, cold plasma pretreatment power, and drying temperature.…”
Section: Resultsmentioning
confidence: 92%
“…The regression model of drying rate has a coefficient of determination ( R 2 ) of 0.9876, adjusted R 2 of 0.9717 and RMSE of 0.0775. The good statistical indexes ( R 2 and RMSE ) suggests the experimental data conform to the model (Abasi, Minaei, & Khoshtaghaza, ; Khoshtaghaza, Khojastehnazhand, Mojaradi, Goodarzi, & Saeys, ). Drying rate is influenced by the cold plasma pretreatment time, cold plasma pretreatment power, and drying temperature.…”
Section: Resultsmentioning
confidence: 92%
“…Wang et al developed multivariate regression models based on the spectral data from commercial crisp grass carp (Ctenopharyngodon idellus) fillets to predict their hardness attributes using the spectral information in the VNIR spectral range [43]. Another research study demonstrated that the use of hyperspectral images in the SWIR spectral range is also suitable for the estimation of texture features in rainbow trout (Oncorhynchus mykiss) fillets [44]. The results of these studies showed high correlation between the predicted texture values fromthespectraldataandthetexturemeasurements.…”
Section: Quality Characterizationmentioning
confidence: 99%